Comparative analysis of the ftness of Drosophila virilis lines contrasting in response to stress - E. K. Karpova; I. Yu. Rauschenbach; N. E. Gruntenko (Вавиловский журнал генетики и селекции)
One of the crucial elements contributing to the adaptation of organisms to unfavorable environmental conditions is the reaction of stress. The study of its genetic control and role in adaptation to unfavorable conditions are of special interest. The juvenile hormone (JH) acts as a gonadotropic hormone in adult insects controlling the development of the ovaries, inducing vitellogenesis and oviposition. It was shown that a decrease in JH degradation in individuals reacting to adverse conditions by stress reaction (Rindividuals) causes delay in egg laying and seems to allow the population to “wait out” the unfavorable conditions, thereby contributing to the adaptation at the population level. However, monitoring natural populations of D. melanogaster for the capability of stress reaction demonstrated that they have a high percentage of individuals incapable of it (NRindividuals). The study of reproductive characteristics of R and NRindividuals showed that under normal conditions Rindividuals have the advantage of procreating oﬀspring. Under unfavorable conditions, if the stressor is intense enough, NRindividuals die, but if its intensity is low, then they, unlike Rindividuals, continue to produce oﬀspring. Based on these data, it was hypothesized that the balance of R and NRalleles in the population ensures its adaptation under frequent stresses of low intensity. To verify the hypothesis by an experiment, the ftness characteristics (lifespan, fecundity) of the R and NR lines of D. virilis were studied under normal conditions and under regular heat stress of various frequency.